Human Lumbar Ligamentum Flavum Anatomy for Epidural Anesthesia: Reviewing a 3D MR-based Interactive Model and Postmortem Samples. Issue 3 (September 2016) - Reina, M.A.; Lirk, P.; Puigdellívol-Sánchez, A.; Mavar, M.; Prats-Galino, A.
Abstract : ( Anesth Analg . 2016;122:903–907) The ligamentum flavum (LF) is an important structure for sensing loss of resistance, which is the technique used to find the epidural space when administering epidural anesthesia. However, due to individual variations, midline gaps, and inherent anatomical characteristics, there can be variations in the structure of the LF that make it difficult to accurately determine loss of resistance. The authors created an interactive 3-dimensional (3D) model of the spine using magnetic resonance imaging (MRI) images from healthy patients. In this article, they compared this reconstruction to results from cadavers to test the model and better determine the shape and structure of the LF.